Study on miscibility and degradation behavior of polylactic acid / thermoplastic polyurethane blends - Buys, Yose Fachmi; Anuar, Hazleen (2018)
Polylactic acid (PLA) has attracted tremendous interest to be used as an alternative to replace the petroleum-based polymers as it possesses good biodegradability, can be derived from renewable sources and shows high mechanical strength. However, its inherent brittleness and low toughness has limited its usage in broader applications. In this work, PLA was melt blended with tough thermoplastic polyurethanes (TPU) in order to produce ecofriendly polymeric materials with balanced mechanical properties. Moreover, the miscibility and the hydrolytic degradation behavior of PLA/TPU blends were also investigated as it is important to control materials degradation behavior in some applications. Five compositions of specimens were prepared by melt blending PLA with TPU using an internal mixer, followed by compression molding. Tensile and impact tests were performed to evaluate the mechanical properties. From the tests, it was apparent that the elongation-at-break and impact strength of the blends increased, as the TPU content increased. Dynamic Mechanical Analysis (DMA) and Scanning Electron Microscopy (SEM) observation were conducted to evaluate the miscibility of PLA/TPU blends. DMA results of the blends revealed two tangent delta peaks, indicated that the blends were immiscible, and the sea-island structure appeared at PLA/TPU 75/25 vol% SEM photograph supported this trend. Finally, hydrolytic degradation behavior of PLA, TPU, and PLA/TPU blends was investigated by measuring the weight loss after immersion the specimens in alkaline solution at predetermined time. It was found that the degradation behavior is affected by blend composition, where PLA/TPU 50/50 vol% showed the fastest degradation rate. This unique result might be ascribed to the cocontinuous morphology shown in the PLA/TPU blend 50/50 vol%.